Images of Bliss : Ejaculation, Masculinity, Meaning - Aydemir, Murat (Book collections on Project MUSE., 2007)
Aristotle believed semen to be the purest of all bodily secretions, a vehicle for the spirit or psyche that gives form to substance. For Proust's narrator in Swann's Way, waking to find he has experienced a nocturnal emission, it is the product of "some misplacing of my thigh." The heavy metal band Metallica used it to adorn an album cover. Beyond its biological function, semen has been applied with surprising frequency to metaphorical and narratological purposes. In Images of Bliss, Murat Aydemir undertakes an original and extensive analysis of images of male orgasm and semen. In a series of.